Penerapan Model Discovery Learning pada Pembelajaran IPA Materi Tekanan untuk Meningkatkan Hasil Belajar Siswa - Fitriana, Fitriana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The purpose of this study was to improve the student learning outcomes of grades VIII.1 SMP Negeri 4 Tanjung in learning science subject matter through the application of Discovery learning models. This research used classroom action research with 29 research subjects. The research instruments used were observation sheets and tests. Data of this research were analyzed through descriptive qualitative and qualitative analysis techniques. The result of the study showed that the average evaluation results in the first cycle, second cycle and third cycle were 61.03, 75.10 and 83.72 with classical completeness of each cycle was 55, 17%, 72.41% and 89.66%. From the learning outcomes, it indicated that there was an increase in the average value from cycle I to cycle II, cycle II to cycle III which proves student learning outcomes. Therefore, it can be concluded that the application of Discovery learning models in the learning of science subject matter can improve student learning outcomes of grades VIII.1 SMP Negeri 4 Tanjung in the academic year 2018/2019.